Game Prototype for Daily English Practice: An Approach Design by using a Puzzle, Riddle and Adventure Scenario - Chaidir Ali; Ronald Thiodorus; Ida Bagus Kerthyayana Manuaba (Bina Nusantara University, 2016)
English language is one of many languages which has been used to communicate around the world. In era of global competition, where most people do interaction borderless, language plays an important role as communication tool. However, many people in the countries where English is a second language, where they rarely speak English in daily life, it could cause lack of confidence which is leading them to be left behind in global competition. In forestall this issue, it is important for people to practice English since early stages of education and use it in daily activity. This paper proposes an alternative solution to improve confidence in learning English in fun way. By creating educational game that can be played in daily activity, it is expected could help people, especially young generation, to improve confidence in practicing English.